Tour guiding or tour misleading? Multifaceted approach in assessing the standards of cultural tour guiding in Bali Island - Chong, Daniel Ka Leong *; Lo, Mun U (Department of Recreation, Park, and Tourism Sciences at Texas A&M University and Texas Digital Libraries, 2021)
This study inspects the quality of tour guiding in Bali Island in specific to cultural tour. A total of 4 quality standards of tour guiding were conceptualized based on suggestions from UNESCO, and World Federation of Tourist Guide Association namely 1) Knowledge, 2) Guiding techniques, 3) Compliance to Rules and Regulations, and 4) Sensitiveness. This study applied 3 research techniques: (1) In-depth Interview, (2) Site observation with experiential audit and (3) Mystery shoppers in collecting data pertaining to perception, experiences, sharing of information, actions and behavior in a natural setting. Total of 2 industrial experts, 7 cultural sites, 15 tour operators, 12 tourists and 2 non-local tour guides were sampled for interview, observation and evaluation. Thematic analysis was used to discover the overall indicators of performance followed by benchmarking analysis to conclude on the level of compliance. Findings suggested that the sampled tour guides did show certain degree of compliance especially in guiding techniques, and sensitive towards tourist’s need. However, findings indicate a concerning gap in standards related to knowledge and abiding rules and regulations. The study also discovers that the performance of tour guiding varies and somehow related to the presence of illegal tour guiding in the island. This study has contributed to the understanding tour guiding qualities in Bali Island. Moreover, this study provides practical and realistic implications that contribute to the development of cultural tour guiding in Bali Island.